Carte de l'AmeÌrique septentrionale. - Delamarche (1838)
Map shows geography, cities, towns of early nineteenth century North America. Inset depicts the Bering Sea and Aleutian Islands. Relief shown by hachures. Scale [ca. 1:22,528,000].